NETWORKING PARADIGM FOR DISTRIBUTED SENSOR NETWORKS - Sitharama Iyengar, S.; Wu, Qishi; Rao, Nageswara S. V. (International Journal of Computing, 2014)
An increasing number of distributed sensor networks are being deployed in a wide spectrum of scenarios for both military and civilian applications. The design of such systems requires the integration of many methods for solving various problems ranging from sensor deployment, through data communication, information fusion to environmental inference and hypothesis testing. This paper is focused on the network aspects in support of data communication services. We present some recent developments in networking techniques for multiple sensor systems in three topics: efficient mobile agent routing in mobile agent-based distributed sensor networks, bandwidth aggregation using multiple paths in wide-area wireline networks, and connectivity enhancement using node movements in small-area wireless mobile ad-hoc networks.